2015
DOI: 10.15344/2455-7498/2015/104
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Evaluation of Aspects Concerning Validity and Feasibility of the Mini Balance Evaluation System Test in a Specialized Rehabilitation Hospital

Abstract: Background: To evaluate aspects of validity and feasibility of the Mini Balance Evaluation Systems Test (Mini-BESTest), for use in a specialized rehabilitation facility on a regular basis. Design: Descriptive cross-sectional study. Methods: A total of 29 physiotherapists (PT) tested 38 male and 21 female patients 20-76 years of age with spinal cord injury (n=20), traumatic brain injury (n=17), acquired brain injury (n=9), multiple trauma (n=6) and other neurological diagnosis (n=7). Dynamic balance was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, the simultaneous presence of two physiotherapists has been suggested during the assessment of patients with severe cognitive or physical impairments (Roaldsen et al, 2015). This would result in higher costs in terms of human resources, but dynamic balance requires more ability than static balance control, and more challenging items (both for the patient and for the raters) are needed for a thorough study of balance performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, the simultaneous presence of two physiotherapists has been suggested during the assessment of patients with severe cognitive or physical impairments (Roaldsen et al, 2015). This would result in higher costs in terms of human resources, but dynamic balance requires more ability than static balance control, and more challenging items (both for the patient and for the raters) are needed for a thorough study of balance performance.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the score could differentiate adults with a SCI walking with/without walking aids and those having low/high concerns about falling. No ceiling effect was mentioned in any previous study (Chinsongkram et al, 2014;Chiu and Pang, 2017;Goljar et al, 2017;Hamre, Botolfsen, Tangen, and Helbostad, 2017;Jacome, Cruz, Oliveira, and Marques, 2016;Jørgensen et al, 2017;Marques et al, 2016;Roaldsen, Wakefield, and Opheim, 2015;Schlenstedt et al, 2015). However, the test-retest and inter-rater reliability, as well as the minimal detectable change (MDC), have not yet been established in adults with SCI in a rehabilitation setting.…”
Section: Introductionmentioning
confidence: 92%
“…It is more clinically applicable than its longer version (15 minutes vs 45 minutes) (Franchignoni et al, 2015) and assesses 14 items coming from 4 of the 6 BESTest components of standing balance: anticipatory postural control (subscale I: 3 items), reactive postural control (subscale II: 3 items), sensory orientation (subscale III: 3 items) and dynamic gait (subscale IV: 5 items). Roaldsen, Wakefield, and Opheim (2015) explored the usefulness of the mini-BESTest for the rehabilitation of adults with various diagnoses, including SCI.…”
Section: Introductionmentioning
confidence: 99%
“…The BESTest is organized around the systems underlying balance control and, similar to the Physiological Profile Approach, it takes over 30 min to administer; however, it has good reliability and a higher sensitivity to change than the BBS [11]. Its short version, i.e., the mini-BESTest, takes only ∼15 min to administer and has good reliability and discriminative validity between fallers and nonfallers [12], yet the reported scores vary widely and suggest a floor effect in patients with a spinal cord injury, a traumatic brain injury, an acquired brain injury, and multiple traumas [13]. Static posturography measures static balance and correlates poorly with dynamic balance [14].…”
Section: Introductionmentioning
confidence: 99%